Developing high quality Android applications : tools and techniques to reduce defects and create maintainable software - Davis, Annyce (O'Reilly, 2015)
"In this Developing High Quality Android Applications training course, expert author Annyce Davis teaches you how you can reduce defects and create maintainable software. This course is designed for users that already have a basic working knowledge of developing Android applications. You will start by learning about Android libraries, then jump into learning about software design principles, including separation of concerns and Law of Demeter. From there, Annyce will teach you how to architect the presentation layer. This video tutorial also covers topics such as model view presenter pattern, static code analysis, PMD, FindBugs, and Android Lint. You will also learn about unit testing, unit testing with JUnit, and user interface testing. Finally, you will learn about user interface testing with Espresso. Once you have completed this computer based training course, you will have gained the knowledge necessary to develop high quality Android applications. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.